JENIS-JENIS FITOPLANKTON DI PERAIRAN RAWA LEBAK TADAH HUJAN PAMPANGAN - Dina Muthmainnah (Universitas PGRI Palembang, 2014)
Rain-fed swamp is a type of freshwater swamp found in Pampangan Sub district of Ogan Komering Ilir Regency,South Sumatra, characterize by fluctuation of water level related to variation of rain precipitation. This research was carried out in Pampangan swamp by collected phytoplankton samples in 5 different month i.e. May, July, October and December 2011 and February 2012 in order to find out the diversity of phytoplankton in rain-fed swamp. Phytoplankton samples were collected by filtering 100 L swamp water through plankton net and 50 ml of filtrate were used for identification. Water quality parameters such as ph, alkalinity, hardness, conductivity, total-P, total-N, and Chlorophyll-a content also observed. The result showed that phytoplankton community in rain-fed swamp composed of 40 species member of 3 class; Bacillariophyceae (22 species), Chlorophyceae (14 species), and Cyanophyceae (4 species).Â Key words: Phytoplankton, rain-fed swamp, Pampangan